Pola Komunikasi Organisasi Komunitas Da’i Di Universitas Islam Negri K.H Saifuddin Zuhri Purwokerto Dalam Meningkatkan Solidaritas Keanggotaan - Ani Safitri; M. Dery Dinata (STIKes Ibnu Sina Ajibarang, 2024)
This research is motivated by the communication patterns applied by the Dai community in increasing solidarity between members of the dai community. The purpose of this study is to analyse how the communication patterns used by members of the dai community in increasing the solidarity of their members. This type of research uses qualitative research. Informants were selected using purposive sampling, whose informant criteria included members of the dai community. Data collection techniques in this study are observation, interviews and documentation. The data analysis technique used in this research is by observing, interviewing and also drawing conclusions. What is obtained from the results of this study is the star model communication pattern, which is the communication pattern used by the preacher community, where all members of the preacher community have the same position and activities within the community also have the same position so as to create strong solidarity between fellow members of the preacher community and can manage messages well so that they can be delivered comfortably.